Counseling Guideline of Spiritual Cognitive Behavior Technique to Optimize Students’ Personality Potential - Ryan Hidayat Rafiola; Jumadi Mori Salam Tuasikal; Aisyah Ummu Hamidah; Alfaiz (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Personality problems among university students, such as identity crises, low self-confidence, and difficulties in self-regulation, indicate that their personality potential has not been fully optimized. This study aims to develop a counseling guideline, the Spiritual Cognitive Behavior Technique to Optimize Students’ Personality Potential (SCBTec-SPP), as an innovation in counseling services. The research employed a research and development approach using the Borg and Gall model, limited to the first five stages: research and information collecting, planning, developing a preliminary form of product, preliminary field testing, and main product revision. The research subjects consisted of 100 students for the preliminary study, 3 experts (media, content, and counseling practitioners), and 35 students for the practicality test. The research instruments included the Student Personality Potential Questionnaire, expert validation sheets, and a practicality questionnaire. Data were analyzed using percentage techniques and the Content Validity Index (CVI). The results showed that the counseling guideline was deemed feasible with an average expert validation score of 86.1% and was practical to use with an S-CVI/Ave score of 0.83, indicating that the SCBTec-SPP counseling guideline is feasible, practical, and has the potential to enhance the quality of counseling services.